2019
DOI: 10.1007/s42452-019-0767-y
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and dry sliding wear study of Al6061/mussel-shell particulate composites

Abstract: Considering the combination of the good physical-mechanical property of mussel shell (MS) and its bulk availability at low processing cost, in present work an attempt has been made to use it as reinforcing particulate material for fabricating Al6061/MS composite through stir casting route. The composite is fabricated with 2, 4, 6, 8 and 10 weight percent (wt%) of mussel shell reinforcement. Microstructural characterization revealed the fair distribution of particles in the matrix. Fabricated matrix with 6 wt% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Currently, the wastes utilized in these studies are divided into two categories: agricultural and industrial wastes. The agricultural wastes have focused on areas including rice husk [6,7], palm kernel fibers and shells [8,9], mussel shells [10,11], and periwinkle shells [12,13]. On the other hand, industrial wastes constitute a wide variety of options such as metallurgical slags [14,15], red mud [5,16], fly ash [17,18], slate powder [19], and brick dust [20].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the wastes utilized in these studies are divided into two categories: agricultural and industrial wastes. The agricultural wastes have focused on areas including rice husk [6,7], palm kernel fibers and shells [8,9], mussel shells [10,11], and periwinkle shells [12,13]. On the other hand, industrial wastes constitute a wide variety of options such as metallurgical slags [14,15], red mud [5,16], fly ash [17,18], slate powder [19], and brick dust [20].…”
Section: Introductionmentioning
confidence: 99%
“…With increase in the applied load and sliding distance, the wear loss of the composites was increased as compared to the base alloy. Dwiwedi et al [19] studied the wear behavior of AA6061 composites reinforced with mussel shell particles where they reported that the sliding wear behavior of the composites was improved as a result of the addition of the mussel shell particles. The wear rate of the MMCs was reduced with higher sliding distances for different loading conditions whereas the cumulative wear loss was increased.…”
Section: Introductionmentioning
confidence: 99%